Management of Orthopaedic Injuries following 2015 Gorkha Earthquake: Our Experience in Public Health Concern Trust Nepal - Prakash , Shikshya; Bogatee, Umesh Bahadur; Shrestha , Roshan Lal; Dangal , Ganesh; Shakya , Anil; Shrestha , Niraj; Bijuchhe , Anuj Raj; Dangal , Ojash (Europasian Journal of Medical Sciences, 2021)
Background: On April 25 2015, a magnitude of 7.8 earthquake struck in central Nepal, causing a huge physical and social disturbances. Physical impacts comprised casualties with deaths and injuries and damage to infrastructure, cultural heritage and natural environment while social impacts are demographic, psychological and economic consequences. We report our experience in treating victims who were brought at our centre via different means. Objectives: to provide an overview the caseload and provide analysis of earthquake victims for improving the future strategies in similar scenarios. Methods: A retrospective study of the clinical characteristics and patterns of hospitalised patient after the 2015 earthquake was conducted. Demographic evaluation, surgical procedures and morbidities were reviewed. The patients were followed up for an average of 24 months, detail records were kept on their recovery and function. Results: A total of 85 patients were treated with subsequent follow-up. The proportion of males admitted was similar to that of females (49.4% and 50.5% respectively). The highest number of admitted age group ranges (17- 45) was about 37.64%. Most injured site was lower limbs (68.23%) where fracture tibia and fibula had the highest incidence (56.89%). Out of all, 14.11% of cases were open fractures. Trauma severity was assessed with injury severity score and most of them categorized as mild one (95.29%). The most common procedure performed was closed reduction and pinning (n=28), followed by open reduction and fixation (n=24). Overall, mortality rate was 2.35% (2 of 85). Total 25 implants were removed within three years of period and 28.6% of patients were not returned to date. Conclusions: The injury epidemiology reported in this study showed quite congruence with most other earthquake related studies. Analysis profiles of injuries and clinical features of earthquake victims will definitely impact rescue efforts and treatment of fracture injuries in possible future natural calamities. DOI: https://doi.org/10.46405/ejms.v3i2.335